Phonetic alignment of speech using continuous density hidden Markov models - Van der Merwe, C. J.(Charl Johannes) (Stellenbosch : Stellenbosch University, 2012)
Study project (M. Elec. Eng.) -- University of Stellenbosch, 1991.